Pengolahan Kelapa Menjadi Minyak Vigin Coconut Oil (VCO) Sebagai Upaya Peningkatan Pendapatan Ekonomi Masyarakat Desa Sri Kuncoro Bengkulu Tengah - Mochamad Ridwan; Lela Rospida; Ririn Nopiah (UNIB Press, 2023)
The aim of community service activities in Sri Kuncoro Village is to socialize the benefits of coconut trees to the local community. Apart from that, to develop a sense of love for the environment through the use of local coconut trees around people's homes and to introduce ways to process coconuts in a more innovative way that has high added value, namely into VCO oil (Virgin Coconut Oil). The process of making coconuts into